EVALUATION OF LAND MONITORING AND CONTROLLING OF BANDUNG CITY GOVERNMENT - Kurniati, Fitrina; Nugraha, Nugraha; Purnamasari, imas; Heryana, Toni (International Journal Accounting Tax and Business, 2021)
An unoptimized land supervision and control stirs up an agrarian conflict in Bandung city. This is proven by the number of lawsuits towards the assets belong to Bandung City Government. Therefore, to avoid the problem from rising in the future, the government of Bandung needs to have a standard for land supervision and control. The result of the study is the SOP for the Lands Supervision and Control of Bandung City Government towards the usage and utilization. Therefore, The City Government of Bandung hopefully can declare the SOP related to the Land Supervision and Control of Bandung City Government which has been designed and agreed altogether, prepare an adequate human resource to run the Main Duty and Functions as well as SOP and design the Academical Text where the Mayor Regulation related to the Lands Supervision and Control of Bandung City Government can be stipulated.